Guidance for hospital and community-based health services for older adults: The senior friendly care framework. (January 2022) - Ryan, David P.; Zeh, Wendy A.; Rozo, Jesika Viviana Contreras; Liu, Barbara A.
Highlights: Health services for older and especially frail adults need improvement. Improvements require the co-evolution of hospital and community-based care. A framework guiding hospital development was adapted to meet intersectoral needs. Older adults, caregivers and intersectoral experts made evidence-informed decisions. A senior friendly care framework can guide intersectoral service improvements. Abstract: To meet the needs of a population of older adults at risk of becoming frail in the context of known limitations to current practice, frameworks have emerged to guide health service development. Typically these frameworks have developed in the hospital sector despite the need for hospital/community sector co-development and adoption. In the present study one such framework – the Senior Friendly Hospital (SFH 1 ) Framework – is examined with an intersectoral lens. The study included a scoping review of literature addressing system-based approaches to improving healthcare of older people as well as a modified Delphi process to incorporate these findings into an expanded framework. Qualitative analysis of the data extracted from the scoping review resulted in the identification of "senior friendly" excerpts that were charted using an apriori matrix provided by the SFH Framework. Researchers conducted thematic analysis of the excerpts to avoid redundancy and wrote statements to optimize thematic clarity. In a modified Delphi process, the statements were subsequently rated for perceived importance, clarity and fit by an intersectoral panel of experts resulting in a refined Senior Friendly Care (sfCare 2 ) Framework comprising 31 statements and 7 guiding principles to consider when implementing improvements in the care of older adults. Finally, a panel of stakeholders were consulted for feedback on the clarity of the framework's intent and its anticipated impact on care. The sfCare Framework is now available to guide hospital and community-based health service development for older adults.